Detektion und Klassifizierung unterschiedlicher Bedeckungen auf Abschlussscheiben von LiDAR-Sensoren - Trierweiler, Manuel (Spektrum der Lichttechnik, 2022)
By providing a high resolution at high distances in a broad field of view, LiDAR sensors are a key element in automated driving cars. However, in harsh environmental conditions, particles from rain or dust attach on the outer surface of the sensor and cause a degradation of the overall performance. This work introduces several methods to detect and characterize those particles, realizing the integration of an intelligent and fully automated cleaning system to restore the required performance.